1996
DOI: 10.1046/j.1365-2249.1996.32737.x
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine in bronchoalveolar lavage fluid (BALF) is an inhibitor of eosinophil-active cytokines

Abstract: Eosinophils and eosinophil granule proteins may play an important role in the pathogenesis of asthma. BALF from 40 patients with symptomatic asthma were analysed for cytokine activity by the eosinophil survival assay. BALF from 15 patients showed increased survival activity. Survival activities in BALF from four of these patients were almost completely blocked by anti‐IL‐5 MoAb, and the remaining activities were blocked by anti‐granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), anti‐IL‐3 antibody, or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…It was further demonstrated that lidocaine preferentially inhibited survival and activation of human eosinophils stimulated by cytokines, such as IL-5, IL-3 and GM-CSF, in a concentration dependent-manner (IC 50 ≅ 110 µM). Such an effect did not seem to be accounted for by the blockade of sodium channels and could not be explained by an action on either cytokine receptor expression or cytokine-induced protein tyrosine phosphorilation (Ohnishi et al 1996. Of note, these effects were not due to nonspecific cytotoxicity either, since (i) lidocaine inhibited eosinophil survival by causing apoptosis rather than necrosis; (ii) the mechanism of cell death was clearly time-dependent, requiring at least 24 h of exposure to lidocaine; and (iii) eosinophil survival and superoxide production induced by IgG, PAF or PMA were not modified by lidocaine, indicating that this local anaesthetic was not a general inhibitor of eosinophils ).…”
Section: Local Anaesthetics and Allergic Inflammationmentioning
confidence: 93%
See 1 more Smart Citation
“…It was further demonstrated that lidocaine preferentially inhibited survival and activation of human eosinophils stimulated by cytokines, such as IL-5, IL-3 and GM-CSF, in a concentration dependent-manner (IC 50 ≅ 110 µM). Such an effect did not seem to be accounted for by the blockade of sodium channels and could not be explained by an action on either cytokine receptor expression or cytokine-induced protein tyrosine phosphorilation (Ohnishi et al 1996. Of note, these effects were not due to nonspecific cytotoxicity either, since (i) lidocaine inhibited eosinophil survival by causing apoptosis rather than necrosis; (ii) the mechanism of cell death was clearly time-dependent, requiring at least 24 h of exposure to lidocaine; and (iii) eosinophil survival and superoxide production induced by IgG, PAF or PMA were not modified by lidocaine, indicating that this local anaesthetic was not a general inhibitor of eosinophils ).…”
Section: Local Anaesthetics and Allergic Inflammationmentioning
confidence: 93%
“…Interestingly, lidocaine also inhibits the function of non-excitable cells, particularly inflammatory cells, such as neutrophils, eosinophils, macrophages, mast cells and T H 2 cells, raising the promising possibility of alternative clinical applications on the control of chronic inflammatory diseases, including asthma (Hunt et al 1996, Ohnishi et al 1996, Hollmann & Durieux 2000, Tanaka et al 2002. Ohnishi et al (1996) incidentally discovered that concentrations of lidocaine as high as 10 mM could be detected in the broncoalveolar lavage fluids recovered from asthma patients subjected to bronchoscopy under lidocaine topical anesthesia, and that such an effluent was a strong inhibitor of eosinophil viability in vitro. It was further demonstrated that lidocaine preferentially inhibited survival and activation of human eosinophils stimulated by cytokines, such as IL-5, IL-3 and GM-CSF, in a concentration dependent-manner (IC 50 ≅ 110 µM).…”
Section: Local Anaesthetics and Allergic Inflammationmentioning
confidence: 99%
“…Lidocaine is largely used in clinic as a shortacting local anaesthetic and antiarrhythmic agent [2]. Interestingly, lidocaine also inhibits the function of non-excitable cells, particularly inflammatory cells, such as neutrophils, eosinophils, macrophages, mast cells and TH2 cells, raising the promising possibility of alternative clinical applications on the control of chronic inflammatory diseases, including asthma [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…78,79 Several uncontrolled studies suggest efficacy in mild-to-moderate asthma. A controlled blinded study by Hunt et al 80 in 50 adults with asthma administered 100 mg of lidocaine by aerosol versus saline 4 times/d showed improved FEV 1 , less nighttime awakening, decreased bronchodilator usage, and decreased blood eosinophil counts.…”
Section: Lidocainementioning
confidence: 99%
“…Nebulized lidocaine has already been mentioned as a potential aerosolized anti-inflammatory in asthma [78][79][80] and is a very effective topical anesthetic. Nebulized lidocaine has been purported to relieve the pain of nasogastric tube placement, 117 bronchoscopy, 118,119 and endotracheal intubation, 120 although not all studies show efficacy.…”
Section: Local Anestheticsmentioning
confidence: 99%